2016
DOI: 10.1038/srep38630
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of class II lanthipeptide bovicin HJ50 via an engineered lanthipeptide synthetase

Abstract: Lanthipeptides are a large class of bacteria-produced, ribosomally-synthesized and post-translationally modified peptides. They are recognized as peptide antibiotics because most of them exhibit potent antimicrobial activities against Gram-positive bacteria especially those that are phylogenetically related to producers. Maturation of class II lanthipeptide like bovicin HJ50 undergoes precursor modification by LanM and a subsequent leader peptide cleavage by LanT. Herein, via co-expression of precursor gene bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…As a step toward advancing a biochemical and structure-function understanding of AMS/PCAT transporters and providing a tool for removing leader peptides from RiPP products, we sought to identify protease domains that retained catalytic activity in the absence of the TMD. Previous studies have demonstrated that the N-terminal 150 amino acids of AMS/PCAT proteins constitute peptidase C39 family members that can be expressed as individual active domains (Håvarstein et al, 1995; Furgerson Ihnken et al, 2008; Ishii et al, 2006; Wu and Tai, 2004; Wang et al, 2016). In search of a substrate tolerant protease domain, we first surveyed AMS transporters encoded in gene clusters containing multiple genes for precursor peptides with diverse core peptide sequences, because these proteases are expected to be inherently tolerant with respect to residues in the P’ positions.…”
Section: Resultsmentioning
confidence: 99%
“…As a step toward advancing a biochemical and structure-function understanding of AMS/PCAT transporters and providing a tool for removing leader peptides from RiPP products, we sought to identify protease domains that retained catalytic activity in the absence of the TMD. Previous studies have demonstrated that the N-terminal 150 amino acids of AMS/PCAT proteins constitute peptidase C39 family members that can be expressed as individual active domains (Håvarstein et al, 1995; Furgerson Ihnken et al, 2008; Ishii et al, 2006; Wu and Tai, 2004; Wang et al, 2016). In search of a substrate tolerant protease domain, we first surveyed AMS transporters encoded in gene clusters containing multiple genes for precursor peptides with diverse core peptide sequences, because these proteases are expected to be inherently tolerant with respect to residues in the P’ positions.…”
Section: Resultsmentioning
confidence: 99%
“…The α‐component is 4 times dehydrated peptide with four lanthionine rings ( m/z 3,457.23, Figure f) and the β‐component is 9 times dehydrated with six lanthionine rings ( m/z 3,108.22 without the glycine residue trace, Figure e). For the structure elucidation of RosA peptides, we aim to co‐express RosT p along with recombinant plasmids generated here (Wang, Ge, Zhang, Teng, & Zhong, ), for obtaining roseocin in yield suitable for NMR. However, the purification strategy for the untagged peptides will have to be worked out accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The maturation starts by dehydration of Ser and Thr residues resulting in Dha or Dhb, which is catalysed by LanB, in the case of class I lanthipeptides, by a bifunctional enzyme termed LanM, for class II, the trifunctional LanKC, or LanL in class III and class IV or triprotein synthetases (LanK, LanX and LanY) in class V, respectively ( Fig. 1) [20,[29][30][31][32]. As a second step, the lanthionine rings are formed by a Michael-type addition with a cysteine side chain.…”
Section: Bacteriocins From Gram-positive Bacteriamentioning
confidence: 99%